2000
DOI: 10.1046/j.1365-2249.2000.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Booster immunization of children with an acellular pertussis vaccine enhances Th2 cytokine production and serum IgE responses against pertussis toxin but not against common allergens

Abstract: SUMMARYAcellular pertussis vaccines (Pa) protect against severe pertussis in children. However, serum antibody responses decline quickly after immunization. Studies in animal models suggest that cell-mediated immunity also contributes to protection against Bordetella pertussis, and it has already been demonstrated that Pa induce T cells that secrete type-1 and type-2 cytokines in children. In this study we examined the persistence of the T cell response and the effect of booster immunization in 4±6-yearold chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 38 publications
8
66
0
3
Order By: Relevance
“…In the present study we show that Pa immunization did not enhance the OVA-specific IgE response (Fig. 2B); this suggests that Pa-like vaccines are unlikely to promote atopy and is consistent with the findings of studies of Paimmunized children, which found no significant enhancement of IgE specific to third-party antigens (50). Significantly decreased levels of OVA-specific IgE were observed in mice in group PaBpOVA compared to those in either the PaOVA or the OVA group (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…In the present study we show that Pa immunization did not enhance the OVA-specific IgE response (Fig. 2B); this suggests that Pa-like vaccines are unlikely to promote atopy and is consistent with the findings of studies of Paimmunized children, which found no significant enhancement of IgE specific to third-party antigens (50). Significantly decreased levels of OVA-specific IgE were observed in mice in group PaBpOVA compared to those in either the PaOVA or the OVA group (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Although OVA-induced sensitization does not impair vaccine-mediated clearance of B. pertussis, it was possible that Pa influenced allergic sensitization. An increase in the concentrations of IgE antibodies specific for PT, a component of Pa, has been reported in other studies (40,50). Therefore, the serum IgE responses of mice sensitized to OVA following Pa or sham immunization were examined.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations